Sensitizing the medical undergraduates to qualitative research: In the context of experiential learning debriefings - Lopamudra Debasish; Kavita Vasudevan; Premnath Dhasaram; Prakash Mathiyalagen (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The role of medical undergraduates is limited while interacting with the community related to issues involving human behavior. Since qualitative research seeks to build a holistic understanding of social phenomena, we designed this project to expose them to the basics of qualitative research in a real-world setting of experiential learning. The aim of this study is to sensitize the medical undergraduates to the basics of qualitative research and able to apply it in the context of experiential learning in the community. MATERIALS AND METHODS: In this current educational intervention, a structured teaching program was designed and applied for the first time, to our students to effectively sensitize them to qualitative research in a natural community setting, intended to provide them a solid base for experiential learning. A batch of students (n = 50) was selected by convenient sampling method who had their clinical postings with us. At first, a "session planning guide" was drawn on the plan of conduction of this program. We followed the "facilitators reference manual by research consortium on educational outcomes and poverty (RECOUP) for our teaching sessions. The framework of our study was executed in the following sequence: sensitization of the learners, exposure to structured quality experience, systematic debriefing sessions with evaluation of learner experiences, and the process and outcome feedbacks from the learners. The students were monitored by trained facilitators. The various study tools used in the structured teaching program included, the teaching sessions using the RECOUP manual, didactic lectures and short group interactive sessions to teach qualitative research and photographs and video clips to facilitate the sessions, mock demonstrations and role plays on interviewing techniques, use of case vignettes on the theme "perception of psychosis" for interviewing the community, structured debriefing guide, and various self-reflective exercises. Learners' perspective of community perception, debriefing sessions, and self-reflective responses were transcribed, and manual content analysis was done to identify the codes and interpret the results. RESULTS: Majority could appreciate the uniqueness of qualitative research over the quantitative counterpart. They could enumerate the attributes of a good qualitative researcher. The debriefing exercises made them summarize their experiences and the self-reflective exercises enabled them to identify their abilities and critique their ideas. It was a different experience to our learners as they could identify themselves with the sentiments of the community. To them, the facilitating points were the interviewing skills and confidence gained in facing the community. However, they felt time constraint for exploring the sensitive issues during the fixed posting schedule. CONCLUSIONS: The experience of learning beyond the boundaries of a classroom setting sensitized them to various community perceptions and reactions. The students perceived the qualitative methods well and could apply the lessons learnt in the facility. They also felt that this learning exposure gave them community orientation and confidence in dealing with community issues.